An Analysis of Feminism in The Movie “Maleficent” by Robert Stromberg - Fitrah Ramadani; Khidayatul Munawaroh; Ridho Pradja Dinata (JELT: Journal of English Language Teaching, 2021)
The research aims to analyze feminism in Maleficent film by Robert Stromberg besides being interested, the research also found that there was an element of women oppression by men where men wanted to control women. This research uses applies qualitative method. The purpose of this research, namely; 1) To the explain type of feminism in the film Maleficent by Robert Stromberg 2) To the explain determine the factors that cause the emergence of feminism in the film Maleficent by Robert Stromberg. The results of this research, the writer had found one kind of feminism that existed in the Maleficent film, namely ecofeminism. For the factors that led to the appearance of feminism in the Maleficent film, the research had found, namely: ecological protection factors and ending domestic violence and abuse factors. The research also found the influence of feminism on the main character, namely: Women and nature are dominated and thus stresses the need for a more interdependent worldview and all living things are essential to the well-being of the planet and that humans are not separate or superior.Key Words: Literature, Feminism, Movie Maleficent